Long non-coding RNAs: new frontiers for advancing personalized cancer medicine in prostate cancer - Ghiam, Alireza Fotouhi; Vesprini, Danny; Liu, Stanley K. (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Long non-coding RNAs (lncRNAs) are a group of non-coding transcripts of more than 200 nucleotides that play important biological and clinical roles in prostate cancer (PCa) tumorigenesis, progression and metastasis. They have also shown potential as a biomarker in the diagnosis and prognosis of this disease. LncRNA prostate cancer associated transcript-14 (PCAT-14) was recently identified as a novel prognostic biomarker in PCa, whose low expression was associated with poor outcomes. Here, we briefly discuss future perspectives and clinical applications of lncRNAs as biomarkers and therapeutic targets for PCa.